Ministry Of Manpower Decree No. 215 Of The Year 2021 Regarding Determining The Children Employment And Training System, The Circumstances And Conditions In Which Employment Takes Place, As Well As The Jobs, Professions And Industries In Which It Is Prohibited To Employ Them = وزارة القوى العاملة قرار رقم 215 لسنة 2021 بشأن تحديد نظام تشغيل وتدريب الأطفال والظروف والأحوال التى يتم فيها التشغيل وكذلك الأعمال والمهم والصناعات التى يحظر تشغيلهم فيها - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic